Écriture visuelle et plastique dans les œuvres de Jan Fabre (Itinera, 2017)
Dealing with the visual aspects in his writing process, this is not only because of the cultural context but also because of his background that Jan Fabre literature is also a visual literature. The analyses of Mon corps, mon gentil corps, dis-moi… focus on the sight sense in a linguistic point of view, and those of Another Sleepy Dusty Delta Day tend to highlight the plasticity of the writing that goes beyond the text itself.